The Role of Digital Economy in Community Income Through Digital Platforms - Putra, Ansari (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The development of the world of technology cannot be denied in human activities. The rapid pace of technology and digitalization has created a digital economy which is characterized by the high development of technology-based business, trade transactions and personal branding which can now be used as income for people in the North Sumatra area. The aim of this research is to examine how the role of the digital economy impacts people’s income through the use of the TikTok digital platform and how big a role the TikTok application plays in people’s income. This research is a type of qualitative research using descriptive methods. The data used is primary data through interviews. The population studied in this research are the people of North Sumatra who use the TikTok application to generate income. The research sample consisted of 3 people. The research data source is primary data obtained by interviews and observation, while secondary data is obtained by documentation. The supporting and inhibiting factors in this research are the ability to know and utilize technological media as supporting indicators for the digital economy.